Mandate, Discretion, and Professionalisation in an Employment Standards Enforcement Agency: An Antipodean Experience. (31st October 2012) - Howe, John; Hardy, Tess; Cooney, Sean
<x xml:space="preserve">Abstract</x> In recent years, there has been a resurgence of scholarly interest in the operation and effect of labour inspectorates around the world. This article aims to contribute to this mounting comparative and socio‐legal literature by considering the emergence of an active and high‐profile enforcement agency in Australia—the Fair Work Ombudsman (FWO). Drawing on the experiences of inspectors and senior managers at the FWO, we examine the structure and mandate of the agency, as well as the discretion afforded to, and the professionalisation of, individual inspectors. While some have sought to draw a distinction between a rule‐bound, specialised approach characteristic of certain Anglo‐American countries and the so‐called Franco‐Iberian model, which places a greater emphasis on flexibility and pragmatism, we found that the FWO does not necessarily fit neatly within this dichotomy. Rather, we observe that as the FWO is a new institution, its mode of operation is in the process of evolution. At present it is pluralistic, in the sense that it exhibits a hierarchical, procedural approach in a drive to address concerns of consistency and accountability, while at the same time allowing, and sometimes encouraging, individuals to be experimental and adaptive.